Refungsionalisasi Kebijakan dalam Meningkatkan Peran Kepemimpinan Perempuan pada Jabatan Birokrasi Pemerintahan di Kabupaten Jayapura - Hikoyabi, Hana S.; Silo, Akbar; Ohoiwutun, Yosephina; Tambaip, Beautus (JURNAL EKOLOGI BIROKRASI, 2022)
This study aims to analyze the refunctionalization of policies in increasing the role of Women's Leadership in the Bureaucracy Position of the Jayapura Regency Government. Therefore, in this study, there are 3 main study focuses, firstly, analyzing the description of the role of women's leadership in Government Bureaucratic Positions in Jayapura Regency. Analyzing the supporting factors and inhibiting factors that affect the leadership role of women in the Government Bureaucracy Position in Jayapura Regency. Third, formulating efforts to refunctionalize policies in increasing the leadership role of women in government bureaucratic positions in Jayapura Regency. The research method used is descriptive qualitative. The research location is in Jayapura Regency. The technique of determining the informants was selected purposively. The data collection used includes in-depth interviews, observations, and FGDs. Data analysis techniques include the stages of data reduction, data presentation, data interpretation and drawing conclusions. The results of the study show that The refunctionalization of gender-based public policies at the district government as an alternative is carried out through two choices of steps, namely direct implementation in the form of programs or through the formulation of derivative policies or derivatives of public policies based on gender mainstreaming. The author's series of investigations in policy implementation starting from programs, to projects and to activities that are in accordance with public sector management show that there are weaknesses in the politics of determining certain positions which are carried out in a closed manner so as to ignore the role of gender mainstreaming.